RANCANG BANGUN DAN UJI TEKNIS ALAT TANAM BENIH JAGUNG (Zea Mays L.) TIPE TP CSM 16 DENGAN TENAGA PENARIK TRAKTOR TANGAN - Pangalila, Nova D. E.; Rantung, Ruland A.; Ludong, Daniel P. M. (Fakultas Pertanian, Universitas Sam Ratulangi, 2020)
AbstractÂ This study aims to design a CSM 16 TP type corn seeds planter by adopting the TP CSM 15 type corn seeds planter and a corn seeds planter integrated with the Kubota M9560 four-wheeled tractor, and testing technically the corn seeds planter covering effective field capacity, theoretical field capacity, field efficiency and planting effectiveness. The results of the study were 1 unit of maize seed planting tool TP CSM 16 type consisting of 2 static planting units, and technical testing of corn seeds planter in 10 m Â 5 m plot of land with 3 repetitions obtained the results is the average effective field capacity of 0,080 ha/hour, the average theoretical field capacity of 0,110 ha/hour and the average field efficiency of 72,54%. The results of field observations on the corn seeds planter is the average distance in row planting is 28,57 cm, the average distance between planting rows is 75,37 cm, the number of seeds per planting hole an average of 1 seed, the average planting depth of 4,23 cm, the percentage of seeds growing an average of 80.42% and the percentage of seeds not growing an average of 19.58%.Â Key words: Seeds planter, TP CSM 16, Hand Tractor.